2022
DOI: 10.3390/ijerph19116574
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Psychological Tolerance under the Haze: A Case Study of Typical Provinces and Cities in China with Severe Haze

Abstract: The interplay of specific weather conditions and human activity results due to haze. When the haze arrives, individuals will use microblogs to communicate their concerns and feelings. It will be easier for municipal administrators to alter public communication and resource allocation under the haze if we can master the emotions of netizens. Psychological tolerance is the ability to cope with and adjust to psychological stress and unpleasant emotions brought on by adversity, and it can guide human conduct to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Another public sentiment study (Adhikary et al 2021) on air pollution mitigation measures found the people's response to be mixed, and those policies were highly criticized. Hswen et al (2019), Sailunaz and Alhajj (2019), Lu et al (2022)used natural language processing techniques to extract and classify sentiment/emotion from the social media posts. Better education and high income lead to a better evaluation of public opinion on air quality in social media (Min et al 2021).…”
Section: Sentiment Analysis Studiesmentioning
confidence: 99%
“…Another public sentiment study (Adhikary et al 2021) on air pollution mitigation measures found the people's response to be mixed, and those policies were highly criticized. Hswen et al (2019), Sailunaz and Alhajj (2019), Lu et al (2022)used natural language processing techniques to extract and classify sentiment/emotion from the social media posts. Better education and high income lead to a better evaluation of public opinion on air quality in social media (Min et al 2021).…”
Section: Sentiment Analysis Studiesmentioning
confidence: 99%
“…Hu [28] used SnowNLP to calculate the emotional tendency of the "COVID-19 in China's big cities" event on the Sina Weibo platform and analyzed the evolution of the microblog emotion of public health emergencies. Lu et al [29] used SnowNLP to calculate the mood scores of Sina Weibo data in China's heavily smoggy areas, providing a new perspective on the impact of haze on human psychology. Tang et al [30] studied the subject development of Sina Weibo by using the LDA topic model to extract themes in various time periods.…”
Section: Introductionmentioning
confidence: 99%